Portuguese and Brazilian students perceptions regarding the flow of knowledge in their courses: two different realities? - Leão, Celina Pinto (2016)
The present study reports findings on students' perceptions in Electrical/Electronic Engineering courses from four higher education institutions: two Portuguese and two Brazilian. This study was based on a questionnaire previously validated that contains two main parts: student characterization and a list of forty-four items, divided in six groups (Teacher Involvement Perception, Student Interest, Student-Teacher Interaction, Course Organization and Functioning, Infrastructures and Overall Satisfaction). Students classified each item in accordance with their level of agreement (1, Strongly Disagree, to 5, Strongly Agree). The main goal of the research was to look for the evolution of a set of these items along the first three curricular years and assess similarities and differences among courses and higher education institutions considered. The set of items was chosen in a way to achieve a better understanding of how the flow of knowledge in these courses is perceived in apparently different realities. The results show that, in general, students do not understand the flow of knowledge along the first three years of study. Despite the differences observed among the four higher education institutions, those differences do not lead to different realities between the two countries.